Global epidemiology and resistance-related mutations of ceftazidime-avibactam-resistant Klebsiella pneumoniae strains - Xie, Xinya; Chen, Jiali; Qi, Lihua; Yuan, Yue; Long, Jiamin; Wu, Xuelian; Liu, Yuan; Guo, Jinpeng; Wang, Changjun; Meng, Xiangzhao; Liu, Xiong; Chen, Yong; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveCarbapenem-resistant Klebsiella pneumoniae (CRKP) infection has become a global public health problem in recent years. However, ceftazidime-avibactam-resistant (CAZ/AVI-R) Klebsiella pneumoniae (K. pneumoniae) has emerged during treatment for CRKP infection. Therefore, understanding the molecular epidemiological characteristics and resistance-related mutations of global CAZ/AVI-R K. pneumoniae strains is crucial for guiding the rational use of CAZ/AVI and for implementing the control measures to prevent the spread of CAZ/AVI-R K. pneumoniae.MethodsNon-repetitive K. pneumoniae strains isolated from clinical and sewage samples from three hospitals were subjected to antimicrobial susceptibility testing (AST) and whole-genome sequencing (WGS). According to the E-test results, 37 and 11 CAZ/AVI-R K. pneumoniae strains were included from clinical and sewage samples, respectively. After applying the inclusion and exclusion criteria and carrying quality control, 253 CAZ/AVI-R K. pneumoniae strains with genome sequences were retrieved from public databases. Sequence types (STs) and serotypes were identified using Kleborate. Antimicrobial resistance genes (ARGs), virulence factors, and plasmids were annotated using Abricate. Insertion sequences (ISs), prophages, and macromolecular secretion systems were predicted using ISEScan, Dbscan, and Macsyfinder, respectively. Prokka, Roary, and IQtree2 were used for annotation, core gene alignment, and phylogenetic analysis, respectively. Mutations in outer membrane porins (OmpK35 and OmpK36) and efflux pumps (AcrA and AcrB) were analyzed and visualized using Miniprot and BioAider.ResultsA total of 301 CAZ/AVI-R K. pneumoniae strains were collected, comprising 37 human clinical strains, 11 sewage-derived strains, and 253 strains from public databases. Through comprehensive annotation, we identified 43 STs, 37 capsular (K) serotypes, 5 O antigen serotypes, 27 plasmid types and 22 ISs, 135 virulence genes, and 10 macromolecular secretion systems were annotated. Prophages carrying ARGs were annotated in 106 strains. The phylogenetic tree was roughly divided into 10 clades based on porins mutations, ARGs, virulence scores, and plasmid types. In total, 128 distinct ARGs were identified among the 301 strains. The ARGs associated with CAZ/AVI resistance in K. pneumoniae strains mainly included the class B metallo-beta-lactamases (MBLs) genes, blaKPC-2, and blaKPC-3 variants. Analysis of porin mutations revealed that in OmpK35, the most common substitution among all strains from three collection sources was at position 28 (*aaK). OmpK36 exhibited the highest number of mutations among strains from three sources, with frequent changes at position 136 (T136G), 137 (-gacacc), and 349 (H349R). Some porin mutations were identified exclusively in strains isolated from hospital clinical samples by our research team. OmpK35 had a substitution at position 132 (E132K). OmpK36 had substitutions at positions 2 (K2S), 3 (V3L), and 146 (R146H), respectively. AcrA and AcrB had substitutions at positions 188 (T188A) and 716 (R716L), respectively. Among the 301 strains, the majority had multiple drug resistance-related mutations, which were extensively distributed across 10 different clades.ConclusionThe combination of multiple drug resistance-related mutations leads to resistance to CAZ/AVI. The most common resistance-related mutations in strains from both public databases and those collected by our team are the coexistence of outer membrane porins and efflux pump mutations, and carriage of MBLs genes.